Why does ingestion of watermelon trigger headache attacks in patients with migraine? - Silva-Néto, Raimundo Pereira; Soares , Adriana de Almeida; Lopes , Luciano da Silva (Headache Medicine, 2023)
Several triggers can trigger a migraine attack, including food. By the way, food only triggers headache in migraine sufferers. The foods that most trigger headache attacks are these: cheese, chocolate, citrus fruits and some sweet fruits, such as watermelon.